Annual Plan 2004-05 Approved Outlay 2004-05 - Planning Commission (Planning Commission, 2004)
State Plan Advisers may kindly refer to D.O. Letter No. M- 13011/1/2003-SP.CO./DCH/11/2004/649 dated 23.8.2004 from Deputy Chairman, ""Planning Commission addressed to Chief Ministers regarding finalisation of Annual Plan 2004-05 of States and Union Territories(UTs) circulated vide letter No. M- 13011/1/2004-SP-Co dated 26.08.2004, copy of which is enclosed, for ready reference. The deadline for receipt of Annual Plan 2004-05 proposals of States and UTs, as indicated in this letter, was 30th September, 2004 and issue of approval letters was scheduled to start from 15th October, 2004. State Plan Advisers are requested to kindly ensure that Annual Plan 2004-05 proposals of the States/UTs under their charge are received by them early and that the approval letters for the Annual Plan 2004-05 are issued within 7 (seven) days from the receipt of such plan proposals.
Planning Commission, State Plan Division